2023
DOI: 10.1002/fsn3.3303
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration modeling and characterization of dehydrated sweet corn

Abstract: The increasing demand of rehydrated foods is due to its better storage stability at ambient conditions and not requiring refrigeration. Prior to drying at 55, 60, 65, and 70°C in a hot air tray dryer, hot water blanching (HB), steam blanching (SB), and microwave blanching (MB) were employed as pretreatments. Rehydration of dried pretreated sweet corn kernel was performed in boiling water. The pretreatments and drying temperatures were independent factors that affected the dependent factors such as rehydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…According to Figure4a, the maximum moisture ratio was revealed during the drying of ZD88 at 35 C, followed by 45 and 55 C. While drying RP909, a comparable pattern was observed in Figure4bindicating the moisture removal rate was faster at higher drying air temperatures than at lower ones. This finding was consistent with(Liu et al, 2021;Nayi et al, 2023), where a high moisture removal rate was observed due to a large temperature difference at the boundary of the product, leading to enhanced heat and mass transfer processes at 55 C. Conversely, a reduced drying rate was associated with low temperatures drying at 35 and 45 C. Moreover, Figure5a,b shows increasing the infrared temperature accelerates the rate of drying, enhancing evaporation, and promoting more significant mass and heat transfer rates. However, when the moisture content is low, reducing the drying temperature helps maintain a consistent evaporation rate throughout the drying process(Li et al, 2021).…”
supporting
confidence: 86%
“…According to Figure4a, the maximum moisture ratio was revealed during the drying of ZD88 at 35 C, followed by 45 and 55 C. While drying RP909, a comparable pattern was observed in Figure4bindicating the moisture removal rate was faster at higher drying air temperatures than at lower ones. This finding was consistent with(Liu et al, 2021;Nayi et al, 2023), where a high moisture removal rate was observed due to a large temperature difference at the boundary of the product, leading to enhanced heat and mass transfer processes at 55 C. Conversely, a reduced drying rate was associated with low temperatures drying at 35 and 45 C. Moreover, Figure5a,b shows increasing the infrared temperature accelerates the rate of drying, enhancing evaporation, and promoting more significant mass and heat transfer rates. However, when the moisture content is low, reducing the drying temperature helps maintain a consistent evaporation rate throughout the drying process(Li et al, 2021).…”
supporting
confidence: 86%
“…The average rehydration ratio of dried SC microwaved for 0, 30, 60, 90, and 120 s were 127.27%, 136.63%, 136.91%, 137.07%, and 136.72%, respectively. Nayi et al ( 2023 ) reported that rehydrated sweet corn obtained from samples treated by microwave‐blanching and drying at 70°C had high maintenance of total sugars, ascorbic acid, geometric mean diameter, and color. The impacts of edible coating and sonication on the rehydration ratio of SC were examined by Salehi, Ghazvineh, and Inanloodoghouz ( 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Constant A 2 allows us to predict the maximum capacity of water absorption. The mentioned model has been widely applied to predict the rehydration course of dried biological materials [39][40][41][42][43][44].…”
Section: Model No Model Equation Model Name Referencesmentioning
confidence: 99%